Vitamins and Mineral Supplements for Retinitis Pigmentosa - Ying Zhao; Kai Feng; Ruibao Liu; Jinhua Pan; Lailin Zhang; Xuejing Lu (Journal of Ophthalmology)
Retinitis pigmentosa (RP) is a group of inherited progressive retinal dystrophies that is present with progressive vision loss, night blindness, visual field reduction, and retinal pigmentation of the fundus. RP is an uncommon but clinically important disease. It is progressive and potentially blinding, and to date, no cure for RP has been identified and clinical interventions to retard disease progression are limited. Because of the nature of this disease, there has been great interest in the development of therapeutic interventions that may prevent its progression or restore the loss of visual function. Studies have indicated a possible role of vitamins and minerals in preventing the progression of RP: vitamin A has been reported to have an important role in the function of retinal photoreceptors; lutein is assumed to play a preventive role in fundus diseases; and docosahexaenoic acid, which is found within photoreceptor cell membranes, may have a functional role in preventing the progression of RP. Therefore, this study aimed to systematically review data from randomized clinical trials (RCTs) evaluating the safety and efficacy of vitamins and mineral supplements for the treatment of RP. We searched through relevant trials in the Cochrane Library, PubMed, Embase, Ovid, AMED, OpenGrey, ISRCTN registry, http://ClinicalTrials.gov, and the WHO ICTRP ranging from the respective dates of foundation to June 18, 2018. We reviewed eight randomized control trials (RCTs) with data for 1231 patients. The results indicated that patients with RP may experience delayed disease progression with vitamin and mineral supplementation. In a broader sense, this review suggests that the future trials on RP patients should consider more vitamins or mineral supplements and other outcome measures from the trials included in this review.